Prevalence and predictors of inappropriate anticoagulation in patients with a CHA2DS2-VASc score of 0 and atrial fibrillation. (1st December 2017) - Saberian, Sepehr; Badin, Auroa; Siebert, Vince; Roy, Ashish; Banga, Sandeep; Ghadiam, Harshavardhan R.; Wigant, Rebecca R.; Aggarwal, Ashim; Baman, Timir S.
Abstract: Background: Previous studies have shown underutilization of anticoagulation therapy in patients with atrial fibrillation and a CHA2 DS2 -VASc score ≥ 2; however there exists little data regarding the inappropriate use of anticoagulation in patients with a CHA2 DS2 -VASc score of 0. We aimed to determine the true prevalence and predictors of inappropriate anticoagulation therapy in patients with atrial fibrillation and a CHA2 DS2 -VASc score of 0. Methods: A retrospective chart review was performed on all patients with atrial fibrillation and a CHA2DS2-VASc score of 0 in our institution from January 2009 to January 2016. Demographic and clinical data were collected from the electronic medical record. We utilized multivariable logistic regression analysis to determine independent clinical predictors of inappropriate anticoagulation administration. Results: 512 patients were identified with a CHA2 DS2 -VASc score of 0 and a diagnosis of atrial fibrillation. Of the 137 patients prescribed anticoagulation, 64 patients were identified as inappropriately treated with anticoagulation therapy after assessing for other indications of warfarin or novel anticoagulant therapy. Independent variables associated with inappropriate anticoagulation administration were age (OR 1.07; 95% CI 1.03–1.10), body mass index (OR 1.06; 95% CI 1.01–1.10), absence of current aspirin use (OR 13.50; 95% CI 6.00–30.54) and persistent atrial fibrillation (OR 2.34; 95% CI 1.11–4.94). Conclusions: Our study shows that 12% of patients with a CHA2 DS2 -VASc score of 0 were inappropriately prescribed anticoagulant therapy. Independent predictors of unnecessary anticoagulation were age, body mass index, absence of current aspirin use and persistent atrial fibrillation.